Activated carbon production method
Patent Information
- Application Number
- CN202210112819.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-29
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2042-01-29
AI Technical Summary
但是,若不能将炭粉较好地融入到活性炭生产工艺中(如添加量过多),也会在一定程度上影响产品的指标
[0031]根据本发明的一种方案,采用炭粉与原料煤按照比例混合、挤压成型,可以使制备出的活性炭的孔隙更发达,从而可以明显提高活性炭产品的碘值,并能增加含氧官能团,以提高活性炭对烟气的脱硫脱硝效果,且使活性炭脱附速度更快。
Smart Images

Figure CN114349003B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for preparing activated carbon, and more particularly to a method for preparing activated carbon by using carbon powder obtained after flue gas treatment to replace part of the raw coal. Background Technology
[0002] During the production of activated carbon, friction occurs between materials and between materials and equipment, generating activated carbon powder. Current technologies typically involve directly burning this powder, thus failing to effectively utilize this resource and maximize its potential. However, this activated carbon powder, having not adsorbed flue gas, contains fewer impurities and can be used as a raw material for re-processing activated carbon. However, if the powder is not properly integrated into the activated carbon production process (e.g., excessive addition), it can negatively impact product specifications. Therefore, how to rationally utilize this activated carbon powder resource has become a pressing issue for the industry. Summary of the Invention
[0003] The purpose of this invention is to provide a method for preparing activated carbon, so as to make full use of the carbon powder generated in the activated carbon production process.
[0004] To achieve the above objectives, the present invention provides a method for preparing activated carbon, comprising the following steps:
[0005] S1. Mix raw coal with pretreated carbon powder to form the first material;
[0006] S2. Add coal tar to the first material and stir evenly to form the second material;
[0007] S3. The second material is formed into a molding compound;
[0008] S4. The molding material is subjected to high-temperature dry distillation to form carbonized material;
[0009] S5. The carbonized material is activated to form activated carbon.
[0010] According to one aspect of the present invention, the pretreatment of the carbon powder involves subjecting the activated carbon powder to flue gas adsorption and grinding. In the pretreatment, the carbon powder is first treated with denitrification flue gas and then treated with desulfurization flue gas.
[0011] According to one aspect of the present invention, the carbon powder is activated carbon powder produced during the activated carbon production process, and the pretreatment includes the following steps:
[0012] a. After screening, it is filled into the desulfurization and denitrification reactor;
[0013] b. Introduce the various gas distributions of the denitrification flue gas into the bypass pipeline of the desulfurization and denitrification reactor. When the gas distribution reaches the preset value in the analyzer, stabilize it for a period of time, and then introduce it into the desulfurization and denitrification reactor. After the carbon powder is adsorbed for a period of time, purge it with nitrogen.
[0014] c. Introduce the various gas distributions of the desulfurization flue gas into the bypass pipe of the desulfurization and denitrification reactor. When the gas distribution reaches the preset value in the analyzer, stabilize it for a period of time before introducing it into the desulfurization and denitrification reactor to allow the carbon powder to be adsorbed for a period of time.
[0015] d. Repeat steps (b) and (c) to complete the pretreatment of the carbon powder and determine the iodine value of the carbon powder.
[0016] According to one aspect of the present invention, the denitrification flue gas comprises oxygen, water vapor, nitric oxide, ammonia, and nitrogen.
[0017] The desulfurized flue gas mixture includes oxygen, water vapor, sulfur dioxide, and nitrogen.
[0018] According to one aspect of the invention, the number of repetitions in step (d) is 5 to 30 times, preferably 15 times.
[0019] According to one aspect of the invention, the volatile content A in the charcoal powder satisfies: A≥5wt%, and the particle size range is 1-5mm.
[0020] According to one aspect of the invention, the flue gas is distributed according to the sintering flue gas of an iron and steel enterprise.
[0021] According to one aspect of the present invention, in step S1, the raw coal is at least one of anthracite, coking coal, and semi-coke.
[0022] According to one aspect of the present invention, in step S1, the raw coal is a mixture of anthracite, coking coal and semi-coke, and the mass ratio is anthracite:coking coal:semi-coke = 1~2:1~3:3~6.
[0023] According to one aspect of the present invention, in step S1, the mass ratio of the anthracite, the coking coal and the semi-coke is anthracite:coking coal:semi-coke = 2:3:5.
[0024] According to one aspect of the present invention, in step S1, the proportion of the raw coal X1 and the proportion of the carbon powder X2 in the first material satisfy: X1+X2≤1, wherein 60wt%≤X1≤99wt%, 1wt%≤X2≤40wt%.
[0025] According to one aspect of the present invention, the amount of coal tar added in step S2 is 28 wt% to 35 wt% of the mass of the first material, and the pitch content of the coal tar is 55 wt% to 65 wt%.
[0026] According to one aspect of the invention, the fineness of the first material satisfies a sieve pass rate of greater than 90% on a 325-mesh Taylor standard sieve.
[0027] According to one aspect of the present invention, in step S2, when coal tar is added to form the second material, the coal tar is added when the temperature of the first material reaches 50-60°C, and the material is kneaded and stirred for at least 10 minutes.
[0028] According to one aspect of the present invention, in step S3, the second material is pressed under a pressure of 5-25 MPa to extrude it into a strip-shaped molding material;
[0029] The particle size of the molding material is 7-11 mm and the length is 0.5-1.5 cm.
[0030] According to one aspect of the present invention, in step S4, the molding material is subjected to high-temperature dry distillation in a carbonization furnace, and the molding material is sequentially moved in the carbonization furnace from the carbonization temperature range of 250-300°C to the carbonization temperature range of 450-500°C and then to the range of 650-700°C, and then discharged from the carbonization furnace discharge hopper to obtain the carbonized material.
[0031] According to one aspect of the present invention, by mixing carbon powder and raw coal in a certain proportion and extruding them, the pores of the prepared activated carbon can be made more developed, thereby significantly increasing the iodine value of the activated carbon product and increasing oxygen-containing functional groups, so as to improve the desulfurization and denitrification effect of activated carbon on flue gas and make the desorption rate of activated carbon faster.
[0032] According to one aspect of the present invention, by reasonably setting the fineness of the raw coal and charcoal powder, it is possible to ensure that a tighter connection is formed between the charcoal particles during the material extrusion molding process, resulting in greater molecular van der Waals forces and thus obtaining a molding material with higher strength.
[0033] According to one aspect of the present invention, by applying high pressure to the material during extrusion, the density of the molded material can be increased, the moisture content can be reduced, and the strength can be increased. Furthermore, by rationally setting the particle size and length of the molded material, the development of its internal pores is facilitated, preventing uneven development of internal pores, resulting in better adsorption performance of the activated carbon product and higher efficiency in the carbonization and activation processes.
[0034] According to one aspect of the present invention, during the dry distillation process, a stepped temperature change initially forms pores inside and outside the molding material. This stepped heating avoids cracking caused by rapid temperature changes, thus ensuring the quality and strength of the carbonized material. Furthermore, high-temperature discharge ensures the carbonized material already possesses a certain level of activity before entering the subsequent activation process, resulting in a shorter activation time and higher efficiency.
[0035] According to one aspect of the present invention, the increased ratio of mesopores to macropores in the carbonized material accelerates both the adsorption and desorption rates of the activated carbon during use, thereby giving the activated carbon excellent desulfurization and denitrification performance. Attached Figure Description
[0036] Figure 1 This is a flowchart schematically illustrating a method for preparing activated carbon according to one embodiment of the present invention;
[0037] Figure 2 The graph shows the relationship between the number of times carbon powder is used for desulfurization and denitrification and the iodine value. Detailed Implementation
[0038] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly described below. Obviously, the drawings described below are merely some embodiments of the present invention, and those skilled in the art can obtain other drawings based on these drawings without creative effort.
[0039] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments. The embodiments cannot be described in detail here, but the embodiments of the present invention are not limited to the following embodiments.
[0040] See Figure 1 The activated carbon preparation method of the present invention firstly mixes raw coal with pretreated carbon powder to form a first material. Then, coal tar is added to the first material and stirred evenly to form a second material. Next, the second material is formed into a molding material, which is then subjected to high-temperature dry distillation to form a carbonized material. Finally, the carbonized material is activated to form activated carbon.
[0041] In this invention, the activated carbon powder is the activated carbon powder produced during the activated carbon production process, and it needs to be pretreated in a desulfurization and denitrification reactor as a raw material. For this purpose, flue gas for adsorption needs to be provided to simulate the sintering flue gas of a steel enterprise. Specifically, the activated carbon powder is first sieved to select powder with a particle size of 1-5 mm and then loaded into the desulfurization and denitrification reactor. Subsequently, the gas source is prepared, mainly including oxygen, deionized water, nitric oxide, ammonia, sulfur dioxide, and nitrogen, to facilitate the subsequent gas distribution of the flue gas through the bypass pipe of the desulfurization and denitrification reactor.
[0042] During pretreatment, the denitrification flue gas is first mixed. Specifically, the bypass pipe is opened to introduce oxygen, water vapor, nitric oxide, ammonia, and nitrogen (as an atmosphere gas) into each flue gas pipe, allowing these gases to combine and form the denitrification flue gas, which then enters the analyzer. When each component reaches its preset value in the analyzer, it is stabilized for 30 minutes. Then, the bypass pipe is closed, and the main pipe is opened, allowing the denitrification flue gas to enter the desulfurization and denitrification reactor. The carbon powder is then allowed to fully adsorb the flue gas in the reactor for 20 hours. After adsorption, high-purity nitrogen at a flow rate of 10 NL / min is introduced as a purging carrier gas for 1 hour. In this embodiment, the preset concentration values of the mixed gas are as follows: O2 concentration is 16% (volume fraction, dry basis), with an allowable absolute deviation of ±0.5% (volume fraction); humidity is 10% (volume fraction), with an allowable absolute deviation of ±0.5% (volume fraction); NO concentration is 400ppm (dry basis), with an allowable absolute deviation of ±10ppm; NH3 concentration is 400ppm (dry basis), with an allowable absolute deviation of ±10ppm.
[0043] Next, the desulfurized flue gas is mixed. First, the bypass pipe is opened, and desulfurized flue gas consisting of oxygen, water vapor, sulfur dioxide, and nitrogen (as an atmosphere gas) is introduced. The mixture is then observed using an analyzer. When each component reaches its preset value, it is stabilized for 30 minutes. Then, the bypass pipe is closed, and the main pipe is opened, allowing the desulfurized flue gas to enter the desulfurization and denitrification reactor. The carbon powder is allowed to fully adsorb the flue gas in the reactor for 5 hours. In this embodiment, the preset concentration values for the mixed gas are as follows: O2 concentration 16% (volume fraction, dry basis), with an allowable absolute deviation of ±0.5% (volume fraction); humidity 10% (volume fraction), with an allowable absolute deviation of ±0.5% (volume fraction); SO2 concentration 1020 ppm (dry basis), with an allowable absolute deviation of ±10 ppm.
[0044] Finally, the above denitrification and desulfurization processes are repeated 5-30 times for each carbon powder. The resulting pretreated carbon powder is then analyzed, and its iodine value is shown in Table 1 below. Figure 2 As shown:
[0045]
[0046] Table 1. Iodine values of carbon powder after cyclic desulfurization and denitrification pretreatment.
[0047] It is evident that the iodine value of the carbon powder rises rapidly in the early stages of the cyclic desulfurization and denitrification pretreatment, but the rise in iodine value tends to level off after more than 15 cycles. Since the time to complete one cycle is approximately 32 hours, the number of cycles is preferably set at 15 to reduce time costs and ensure the representativeness of the carbon powder.
[0048] In summary, this invention does not utilize waste carbon powder from industrial desulfurization and denitrification equipment as raw material. Instead, it uses a formulated gas to simulate sintering flue gas to desulfurize and denitrify pure carbon powder. This not only imbues the carbon powder with functional groups but also reduces impurities. Furthermore, this pure carbon powder originates from the powder produced during activated carbon production, thus fully utilizing this carbon powder resource.
[0049] In this invention, the raw coal is at least one of anthracite, coking coal, and semi-coke, preferably a mixture of anthracite, coking coal, and semi-coke, with a mass ratio of 1-2:1-3:3-6. In this embodiment, the mass ratio of anthracite:coking coal:semi-coke is 2:3:5. Using the above-mentioned proportions of raw coal results in higher quality activated carbon with greater strength, porosity, and activity.
[0050] In the first material, the proportions of raw coal (X1) and carbon powder (X2) satisfy: X1 + X2 ≤ 1, where 60 wt% ≤ X1 ≤ 99 wt%, and 1 wt% ≤ X2 ≤ 40 wt%. As described above, the carbon powder of this invention is obtained by pre-treating activated carbon powder produced during the activated carbon production process through flue gas adsorption and grinding, resulting in activated carbon granules with a particle size less than 0.045 mm, containing a portion of volatile matter. Thus, this invention rationally reuses the activated carbon powder generated during activated carbon preparation, thereby improving the utilization rate of the carbon powder and better leveraging its function. Furthermore, since the carbon powder contains a large number of pores, adding it to the raw material can also promote the development of pores in the raw coal. In addition, because the carbon powder has undergone pre-treatment as described above, it also contains a large amount of volatile matter and a small amount of oxygen-containing functional groups, which is beneficial for improving the desulfurization and denitrification indicators of the activated carbon, resulting in better adsorption performance and other key indicators of the finished activated carbon.
[0051] In this invention, the fineness of the first material meets the requirement that the sieve passing rate on a 325-mesh Taylor standard sieve is greater than 90%, that is, the raw coal and carbon powder respectively reach the above-mentioned fineness, which can ensure that the raw coal particles and carbon powder particles are fully and uniformly mixed, so that the raw coal particles and carbon powder particles can be more tightly connected during the high-pressure molding process, the molecular van der Waals forces are greater, and thus the strength of the resulting molded material is higher.
[0052] In this invention, the second material is pressed under a pressure of 5-25 MPa to form a strip-shaped molding material with a particle size of 7-11 mm and a length of 0.5-1.5 cm. By applying high pressure during the extrusion process, the molding material achieves higher density, lower moisture content, and higher strength. Furthermore, setting the particle size and length of the molding material within the aforementioned range is more conducive to the development of internal pores, avoiding the drawbacks of uneven internal pore development. This results in better adsorption performance of the final activated carbon product and higher efficiency in the carbonization and activation processes.
[0053] In this invention, the molding material undergoes high-temperature dry distillation in a carbonization furnace. Specifically, the molding material is sequentially moved within the furnace from a carbonization temperature range of 250-300°C to a carbonization temperature range of 450-500°C, and then to a range of 650-700°C. The carbonized material is then discharged from the furnace's discharge hopper. This step-by-step temperature change initially forms pores inside and outside the molding material, preventing cracks caused by rapid temperature changes and thus ensuring the quality and strength of the carbonized material.
[0054] In this invention, the carbonized material is activated by reacting with steam in an activation furnace at 900°C to obtain activated carbon. This significantly increases the ratio of mesopores to macropores in the carbonized material, and the formation of these pores accelerates both the adsorption and desorption rates of the activated carbon during use, resulting in excellent desulfurization and denitrification performance.
[0055] The following examples illustrate the activated carbon preparation method of the present invention in detail. In the examples below, the iodine value (mg / g) was determined according to the national standard GB / T7702.15-1987, the abrasion resistance (%) was determined according to the national standard GB / T30202.3-2013, the compressive strength was determined according to the national standard GB / T30202.3-2013, the ash content was determined according to the national standard GB / T7702.15-2008, the desulfurization value was determined according to the national standard GB / T30202.4-2013, and the denitrification rate was determined according to the national standard GB / T35254-2017, as shown in Table 2 below.
[0056]
[0057]
[0058] Table 2
[0059] Example 1
[0060] Referring to Table 1, in this embodiment, anthracite, coking coal, and semi-coke are crushed and ground in a mass ratio of 2:3:5 to obtain raw coal with a fineness that meets the requirement of a sieve passing rate of more than 90% on a 325-mesh Taylor standard sieve; the carbon powder is crushed and ground to a fineness that meets the requirement of a sieve passing rate of more than 90% on a 325-mesh Taylor standard sieve; and the coal tar pitch content meets the requirement of 55wt% to 65wt%.
[0061] Subsequently, raw coal, charcoal powder, and coal tar are weighed and placed into a kneading device. The ratio of anthracite, coking coal, and semi-coke in the raw coal remains unchanged, accounting for 99 wt% of the first material. Charcoal powder accounts for 1 wt% of the first material, and coal tar accounts for 30 wt% of the first material (not included in the total weight of the first material). The raw coal and charcoal powder are added to the kneading device in descending order of mass. The kneading device is heated to a constant temperature of 85℃, and the stirring time is 30 minutes. During the stirring time, the raw coal and charcoal powder are thoroughly mixed. This method of adding materials from large to small mass allows the smaller material to disperse more quickly among the larger material during stirring, resulting in faster and more uniform mixing. When the material temperature reaches 45-50℃, 30 wt% of the coal tar from the first material is weighed and added to the kneading device, and the material is kneaded and stirred for 10 minutes. Under the above kneading and stirring time and material temperature conditions, the lubricating and binding effect of coal tar is fully utilized, preparing for the next step of forming coal particles to bond together. After kneading and stirring, the kneaded material is obtained.
[0062] In this embodiment, a four-column hydraulic press is used to press the kneaded material into strips, which are then granulated to obtain the shaped material. The carbon strips have a particle size of 8.8 mm, a length of 1-1.5 cm, and a molding pressure of 15 MPa. The shaped material is then fed into a carbonization furnace for carbonization and dry distillation to obtain carbonized material. The material moves from a carbonization temperature range of 350°C to 500°C and then to 700°C within the furnace, before being discharged from the furnace outlet for 60 minutes. Finally, the carbonized material is sent to an activation furnace for activation to obtain activated carbon. In the activation process, steam is used as the activation medium. Steam is introduced when the furnace temperature reaches 800°C to create a steam atmosphere during the activation of the carbonized material. When the furnace temperature reaches 900°C, the activation furnace is operated at a constant temperature for 5 minutes to stabilize the furnace temperature at 900±1°C. The carbonized material was fed into an activation furnace for activation reaction for 5 minutes to obtain activated carbon. The resulting activated carbon had the following properties: abrasion resistance 98.23%, compressive strength 47.5 kgf, iodine value 330 mg / g, ash content 12.45%, desulfurization value 15.40 mg / g, and denitrification rate 54.84%. According to the specifications in GB / T30201-2013 "Coal-based Granular Activated Carbon for Desulfurization and Denitrification", this invention can produce qualified activated carbon with excellent abrasion resistance and compressive strength.
[0063] In the following embodiments, the characteristics of raw coal, coal tar, and other materials are different, but their production processes are the same as those described above, so they will not be repeated here.
[0064] Example 2-11
[0065] Referring to Table 2, the difference between Examples 2-10 and Example 1 lies in the content of carbon powder added to the raw materials, while Example 11 does not add carbon powder to the raw materials. Furthermore, Table 2 also shows that the corresponding indicators of the final activated carbon obtained in different examples have changed. Setting the carbon powder content to 1wt%-30wt% maximizes the reuse of carbon powder. The activated carbon prepared using carbon powder has the following indicators: iodine value ≥330mg / g, abrasion resistance ≥97%, compressive strength ≥40kgf, desulfurization value ≥15.4mg / g, and denitrification rate ≥54.8%. In Example 11, without carbon powder, the iodine value, desulfurization value, and denitrification rate all decrease. That is, the activated carbon prepared by mixing carbon powder as one of the raw materials with raw coal has better iodine value, desulfurization value, and denitrification rate. This is related to the porous structure of the carbon powder itself, which contains oxygen-containing functional groups that can catalyze reactions. During coal pyrolysis, the porous structure of activated carbon powder promotes the development of the porous structure in activated carbon, thereby significantly improving the specific surface area and desulfurization and denitrification performance of activated carbon.
[0066] In Examples 1-11, the iodine value, desulfurization value, and denitrification rate gradually increased with the increase of the proportion of carbon powder in the first material. When the proportion of carbon powder was 21 wt%, high-grade activated carbon could be obtained. Therefore, in this invention, using carbon powder to replace part of the raw coal in the first material not only saves the cost of raw materials and produces activated carbon with qualified indicators, but also makes the activated carbon have higher desulfurization and denitrification performance. The indicators show that there is room for improvement in the carbon powder content, so the carbon powder content is not limited to 1 wt%-21 wt%, but can also be greater than 21 wt%.
[0067] Examples 12-14
[0068] In Example 12, activated carbon undersize waste (unqualified material, not treated with flue gas) was used as raw material, and coal tar was used as a binder. Other preparation processes and control parameters were the same as in Example 1. The experimental statistics of the performance of the prepared activated carbon are shown in Table 3 below:
[0069]
[0070]
[0071] Table 3
[0072] It is evident that the activated carbon prepared using undersize activated carbon particles and raw coal as raw materials still exhibits lower iodine value, desulfurization value, and denitrification value than the activated carbon prepared in Examples 1-10. This demonstrates that even when using undersize activated carbon particles and raw coal to prepare activated carbon, the performance indicators of the obtained activated carbon product remain insufficient.
[0073] Examples 15-17
[0074] Examples 15-17 used carbon powder and raw coal generated during the flue gas purification process of steel plants as raw materials, and coal tar as a binder. Other preparation processes and control parameters were the same as in Example 1. The experimental statistics of the performance of the prepared activated carbon are shown in Table 4 below:
[0075]
[0076]
[0077] Table 4
[0078] It can be seen that, compared with the activated carbon generated in this invention, the activated carbon prepared from carbon powder and raw coal produced in the flue gas purification process has similar wear resistance, compressive strength, iodine value and ash content to the activated carbon prepared from carbon powder and raw coal, but its desulfurization value and denitrification rate are lower than those of the activated carbon prepared from carbon powder and raw coal.
[0079] Furthermore, the charcoal powder used in this invention has an iodine value between 300-400 mg / g, an ash content between 12-18%, and a volatile content between 10-15%. The indicators obtained after sampling and testing are shown in Table 5 below:
[0080]
[0081] Table 5 Carbon Powder Indicators
[0082] It is evident that the carbon powder using the indicators in Table 5 has a porous structure composed of a large number of mesopores and micropores, and after pretreatment, it has characteristics similar to the functional groups contained in the carbon powder produced in the steel plant purification process, which significantly improves the desulfurization and denitrification effect.
[0083] The above description is merely an embodiment of the present invention and is not intended to limit the invention. For those skilled in the art, the present invention can have various modifications and variations. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing activated carbon, comprising the following steps: S1. Mix raw coal with pretreated carbon powder to form a first material. The carbon powder is activated carbon powder produced during the activated carbon production process. The pretreatment includes the following steps: a. After screening, the carbon powder is loaded into the desulfurization and denitrification reactor; b. Introduce the various gas distributions of the denitrification flue gas into the bypass pipeline of the desulfurization and denitrification reactor. When the gas distribution reaches the preset value in the analyzer, stabilize it for a period of time, and then introduce it into the desulfurization and denitrification reactor. After the carbon powder is adsorbed for a period of time, purge it with nitrogen. c. Introduce the various gas distributions of the desulfurization flue gas into the bypass pipe of the desulfurization and denitrification reactor. When the gas distribution reaches the preset value in the analyzer, stabilize it for a period of time, and then introduce it into the desulfurization and denitrification reactor to allow the carbon powder to be adsorbed for a period of time. d. Repeat steps b and c to complete the pretreatment of the carbon powder and determine the iodine value of the carbon powder; S2. Add coal tar to the first material and stir evenly to form the second material; S3. The second material is made into a molding material; S4. The molding material is subjected to dry distillation to form carbonized material; S5. The carbonized material is activated to form activated carbon.
2. The method according to claim 1, characterized in that, The denitrification flue gas mixture includes oxygen, water vapor, nitric oxide, ammonia, and nitrogen. The desulfurized flue gas mixture includes oxygen, water vapor, sulfur dioxide, and nitrogen.
3. The method according to claim 1, characterized in that, The number of repetitions in step d is 5 to 30 times.
4. The method according to claim 1, characterized in that, The volatile matter content A in the charcoal powder is ≥5wt%, and the particle size is 1-5mm.
5. The method according to claim 1, characterized in that, The raw coal is at least one of anthracite, coking coal, and semi-coke.
6. The method according to claim 5, characterized in that, The raw coal is a mixture of anthracite, coking coal and semi-coke, with a mass ratio of 1-2:1-3:3-6.
7. The method according to claim 6, characterized in that, The mass ratio of the anthracite, the coking coal, and the semi-coke is 2:3:
5.
8. The method according to claim 1, characterized in that, The proportions of raw coal (X1) and charcoal powder (X2) in the first material satisfy the following relationship: X1+X2≤1; Among them, 60wt%≤X1≤99wt%, and 1wt%≤X2≤40wt%.
9. The method according to claim 1, characterized in that, The fineness of the first material meets the requirement that the sieve passing rate on a 325-mesh Taylor standard sieve is greater than 90%.
10. The method according to claim 1, characterized in that, The amount of coal tar added in step S2 is 28 wt% to 35 wt% of the mass of the first material; The coal tar has a pitch content of 55 wt% to 65 wt%.
11. The method according to claim 1, characterized in that, In step S2, when the temperature of the first material reaches 50-60°C, the coal tar is added and kneaded and stirred for at least 10 minutes.
12. The method according to claim 1, characterized in that, In step S3, the second material is pressed under a pressure of 5-25 MPa to form a strip-shaped molding material; The particle size of the molding material is 7-11 mm and the length is 0.5-1.5 cm.
13. The method according to claim 1, characterized in that, In step S4, the molding material is moved in the carbonization furnace from the carbonization temperature range of 250-300℃ to the carbonization temperature range of 450-500℃, and then to the range of 650-700℃ to complete the dry distillation process and form the carbonized material.
Citation Information
Patent Citations
Method for preparing activated carbon
CN111661846A